1999
DOI: 10.1161/01.str.30.4.800
|View full text |Cite
|
Sign up to set email alerts
|

Cerebral Blood Volume in Acute Brain Infarction

Abstract: Background and Purpose-The aim of this study was to correlate the abnormality in cerebral blood volume (CBV) measured by dynamic susceptibility contrast-enhanced MRI with that in cerebral blood flow (CBF) estimated by single-photon emission CT with [ 99m Tc]hexamethylpropylenamine-oxime in patients with acute ischemic stroke. Methods-Nine patients with unilateral occlusion of either the middle cerebral artery or the internal carotid artery (4 men and 5 women; meanϮSD age, 74.4Ϯ11.6 years) were studied within… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
11
0

Year Published

2001
2001
2021
2021

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 102 publications
(15 citation statements)
references
References 41 publications
4
11
0
Order By: Relevance
“…Cerebral blood volume has been previously reported to be, normal, increased, or decreased after acute brain ischemia, which appears to depend upon the severity of hypoperfusion (Hatazawa et al, 1999). However, there is no information available on changes in vascular volume after ischemia in fetal subjects treated with anti-IL-1β antibody infusions.…”
Section: Discussionmentioning
confidence: 99%
“…Cerebral blood volume has been previously reported to be, normal, increased, or decreased after acute brain ischemia, which appears to depend upon the severity of hypoperfusion (Hatazawa et al, 1999). However, there is no information available on changes in vascular volume after ischemia in fetal subjects treated with anti-IL-1β antibody infusions.…”
Section: Discussionmentioning
confidence: 99%
“…The level of flow decrease that predicts extended infarction or hemorrhagic complications was estimated at different values and varied between complete lack of ECD uptake and a relative decrease in perfusion to 35–60% of the contralateral value [55,56,57]. The threshold for a moderately ischemic area with a good chance of recovery was set at 70% of contralateral tracer uptake in several studies [58, 59].…”
Section: Single-photon-emission Computed Tomographymentioning
confidence: 99%
“…4 We previously reported that total CBV severely decreased in ischemic core in acute stroke patients. 5 The mechanism responsible for upper limitation of OEF would be a restricted D c due to capillary blood volume reduction in ischemic brain. Objectives: QSPECT package has been developed for standardized calculation of quantitative CBF images using I-123 IMP 1 and is appropriate for multicenter clinical studies.…”
Section: Discussionmentioning
confidence: 99%